The ‘Vero Cell’ COVID-19 vaccine rollout in Nepal: What we know about the Chinese vaccine development and access? - Shah, Jay Narayan (Journal of Patan Academy of Health Sciences, 2021)
The world has changed dramatically from the impact of the COVID-19. It has impacted the normality of daily life, highlighting the failure of rich and poor nations alike, which is evident from the high number of human lives lost in rich and powerful countries like the USA with total deaths of 32,735,704 and Europe with 43,708,958 until April 24, 2021, as per Worldometer. The COVID-19 pandemic has shown that all of us ‘have and have-not’, no one can escape from the effects of the lockdowns, disruption of normal life including education, businesses, etc. reminding all of us that equitable access to vaccines is the best possible choice not to further exacerbate the challenges because ‘no country is safe until every country is safe’. It is a remarkable scientific achievement that within a year of the identification of the virus, we have COVID-19 vaccines, albeit available mostly in rich countries. The benefit of research is possible only with solidarity, by sharing the available resources, vaccine included, for the control of the ongoing COVID-19 pandemic.Modern science and technology, including the development and marketing of COVID-19 vaccines, have been focused in the USA and Europe. China joined this club of elites of science following the Chinese FDA approval of Sinopharm (the subsidiary of state-owned China National Pharmaceutical Group- CNPG), first COVID-19 vaccine (inactivated Sars-Cov-2) based on the results of the phase-3 clinical trial in UAE and Bahrain showing up to 86% efficacy of the vaccine in preventing COVID-19.Detail of trials of Sinopharm inactivated COVID-19 vaccines (Vero Cells) available on two early trials in China (Phase I/II ChiCTR2000031809, enrollment 1,456) and later 4 trials outside China (phase III, NCT04510207 Bahrain, Egypt, Jordan, United Arab Emirates- enrollment of 45,000; ChiCTR2000034780 United Arab Emirates, enrollment of 15,000; NCT04612972 Peru, enrollment of 6,000) show the progress of research and approval in China and UAE.Modern science and technology, including the development and marketing of COVID-19 vaccines, have been focused in the USA and Europe. China joined this club of elites of science following the Chinese FDA approval of Sinopharm (the subsidiary of state-owned China National Pharmaceutical Group- CNPG) first COVID-19 vaccine (inactivated Sars-Cov-2) based on the results of the phase-3 clinical trial in UAE and Bahrain showing up to 86% efficacy of the vaccine in preventing COVID-19.3